2016
DOI: 10.1371/journal.pone.0158131
|View full text |Cite
|
Sign up to set email alerts
|

Tail Docking and Ear Cropping Dogs: Public Awareness and Perceptions

Abstract: Tail docking and ear cropping are two surgical procedures commonly performed on many dog breeds. These procedures are classified as medically unnecessary surgeries whose purpose is primarily cosmetic. Available attitude research surrounding these controversial practices has been limited to surveys of veterinarians and dog breeders familiar with both practices. The aim of this project was to: 1) assess public awareness of tail docking and ear cropping, 2) determine whether physical alteration of a dog affects h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
1
15
0
1
Order By: Relevance
“…Some owners may have chosen this appearance without realising its unnatural origin and the surgeries required to create it or the legal implications. An American study analysing participant knowledge of the relationship of certain traits, including ear size and shape in traditionally cropped breeds, to genetics or environment supports this suggestion 20 . Many participants thought the cropped appearance was mostly a genetic trait, with only 58% correctly recognising that ‘some dog breeds have part of their ears and tails surgically removed after they are born’.…”
Section: Discussionmentioning
confidence: 99%
“…Some owners may have chosen this appearance without realising its unnatural origin and the surgeries required to create it or the legal implications. An American study analysing participant knowledge of the relationship of certain traits, including ear size and shape in traditionally cropped breeds, to genetics or environment supports this suggestion 20 . Many participants thought the cropped appearance was mostly a genetic trait, with only 58% correctly recognising that ‘some dog breeds have part of their ears and tails surgically removed after they are born’.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were told that they were participating in a study to assess whether personality traits could be accurately predicted based upon career choice [ 26 ]. Participants were then told they would be reading about a real person.…”
Section: Methodsmentioning
confidence: 99%
“…tail docking dogs, mulesing sheep, and culling day-old male chicks) which are implicitly deemed acceptable in that they receive minimal public attention. Indeed, a Canadian study on public awareness of tail docking and ear croppings in dogs found that the majority of participants held the belief that short ears and tails were the result of genetics as opposed to an intentional act on the part of owners and breeders (Mills et al, 2016). Similarly, a German study on the killing of day-old male chicks in the poultry farming sector revealed that consumers lack considerable knowledge of the practice (Schröter & Mergenthaler, 2019).…”
Section: Destabilising the Welfare-rights Dichotomymentioning
confidence: 99%